Integrasi Hipnoparenting dan Storytelling dalam Keperawatan Komplementer untuk Meningkatkan Konsumsi Ikan sebagai Upaya Mendukung Perkembangan Anak Prasekolah - Alvi Ratna Yuliana (Pusat riset dan Inovasi Nasional, 2025)
Fish plays a vital role in early childhood development due to its high nutritional value, yet consumption among preschoolers in Indonesia remains low. This study explores the effectiveness of combining hypnoparenting and storytelling as a complementary nursing strategy to promote fish consumption in young children. A quasi-experimental design with a pretest–posttest control group was used, involving 30 preschoolers divided into experimental and control groups. The experimental group received a four-week intervention integrating hypnoparenting and storytelling, while the control group received standard education. Dietary intake was assessed using a Food Frequency Questionnaire (FFQ). Results showed a significant increase in fish consumption in the experimental group (p = 0.000), with no significant change in the control group (p = 0.102). The Mann-Whitney U test also confirmed a significant difference between the groups (p = 0.000). These findings suggest that integrating hypnoparenting and storytelling is an effective, family-centered complementary nursing approach to promote healthier eating habits. This innovative method offers potential in supporting preschool children’s nutrition and overall development through engaging and parent-involved strategies.